VARIABEL - VARIABEL PEMBEDA TINGKAT KESEHATAN LPD KECAMATAN KUTA SELATAN - Aryanto, I Putu; Purbawangsa, Ida Bagus Anom (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the variables distinguishing and differentiating the dominant variable LPD soundness District of South Kuta during the period 2010-2014. This research was conducted in LPLPD Badung, Bali Province. Sampling technique used is the technique of the census, the number of samples are 9 LPD. The data analysis technique used is the discriminant analysis. The results showed that the variables consisting of CAR, KAP, CPRR, ROA, ROA, and LDR LACLR a distinguishing variable in distinguishing the soundness of LPD District of South Kuta. The dominant variable that differentiates the soundness of LPD District of South Kuta in this study is CPRR, ROA and ROA. The classification results of discriminant analysis with the simultaneous method (direct) indicates the level of accuracy in classifying the soundness of the model LPD District of South Kuta 2010-2014 period that is equal to 97.7% or occur misclassification of 2.3%.
Keywords: CAR, KAP, CPRR, ROA, BOPO, LACLR and LDR